Given that the function g(x)=x-3/x+4, the evaluation gives:
- g(9) = 6/13.
- g(3) = 0.
- g(-4) = undefined.
- g(-18.75) = 1.07.
- g(x+h) = x+h-3/x+h+4
<h3>How to evaluate the function?</h3>
In this exercise, you're required to determine the value of the function g at different intervals. Thus, we would substitute the given value into the function and then evaluate as follows:
When g = 9, we have:
g(x)=x-3/x+4
g(9) = 9-3/9+4
g(9) = 6/13.
When g = 3, we have:
g(x)=x-3/x+4
g(3) = 3-3/3+4
g(3) = 0/13.
g(3) = 0.
When g = -4, we have:
g(x)=x-3/x+4
g(-4) = -4-3/-4+4
g(-4) = -1/0.
g(-4) = undefined.
When g = -18.75, we have:
g(x)=x-3/x+4
g(-18.75) = -18.75-3/-18.75+4
g(-18.75) = -15.75/-14.75.
g(-18.75) = 1.07.
When g = x+h, we have:
g(x)=x-3/x+4
g(x+h) = x+h-3/x+h+4
Read more on function here: brainly.com/question/17610972
#SPJ1
Based on the given description above, it is said that the graph is made of the length of the side of a square. By definition, a square has equal sides, and the area of getting the square is A=s^2. Therefore, the function rule for this to find the area for any given side length would be y = x^2. Given the y is the area of the graph and x is the length of the side. Hope this answer helps.
Simplify the following:
((8 x^3 y^2 a^2 b^4)/4)^(-2)
8/4 = (4×2)/4 = 2:
(2 x^3 y^2 a^2 b^4)^(-2)
Multiply each exponent in 2 x^3 y^2 a^2 b^4 by -2:
(x^(-2×3) y^(-2×2) a^(-2×2) b^(-2×4))/(2^2)
-2×3 = -6:
(x^(-6) y^(-2×2) a^(-2×2) b^(-2×4))/2^2
-2×2 = -4:
(y^(-4) a^(-2×2) b^(-2×4))/(2^2 x^6)
-2×2 = -4:
(a^(-4) b^(-2×4))/(2^2 x^6 y^4)
-2×4 = -8:
b^(-8)/(2^2 x^6 y^4 a^4)
2^2 = 4:
Answer: 1/(4 x^6 y^4 a^4 b^8) thus the answer is A
Answer:
let remaining angle in heptagon be a.
a+64=180(linear pair)
a=116
again
x+155+90+163+a+121°=720(sum of interior angle of hexagon is (6-2)×180°)
x+529+a=720
x+116=720-529
x=191-116=75
Answer:
C
Step-by-step explanation:
-3+12 = 9
-12+3 = -9
-6+6 = 0
6+6 = 12